2006
DOI: 10.4103/0250-474x.27826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of olibanum and its resin as rate controlling matrix for controlled release of diclofenac

Abstract: Olibanum and its resin and carbohydrate fractions were evaluated as rate controlling matrix materials in tablets for controlled release of diclofenac. Diclofenac matrix tablets were formulated employing olibanum and its resin and carbohydrate fractions in different concentrations and the tablets were evaluated for various tablet characters including drug release kinetics and mechanism. Olibanum and its resin component exhibited excellent retarding effect on drug release from the matrix tablets even at very low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 1 publication
1
17
1
Order By: Relevance
“…Tramadol release from the prepared matrix tablets followed either concentration dependent or independent kinetics, and non-Fickian mechanism. The observed non-Fickian mechanism of drug release was in contrast to the findings of Chowdary et al 16 who reported a Fickian mechanism of drug release. This deviation could possibly related to the nature of polymer matrix.…”
Section: Model Dependent and Independent Analysiscontrasting
confidence: 99%
See 3 more Smart Citations
“…Tramadol release from the prepared matrix tablets followed either concentration dependent or independent kinetics, and non-Fickian mechanism. The observed non-Fickian mechanism of drug release was in contrast to the findings of Chowdary et al 16 who reported a Fickian mechanism of drug release. This deviation could possibly related to the nature of polymer matrix.…”
Section: Model Dependent and Independent Analysiscontrasting
confidence: 99%
“…The difference in drug release between formulations is further supported by MDT values wherein F1 exhibited a lower MDT (112.5 min) than F2 and F3 (Table 2). Similar release profile for diclofenac sodium using resin extracted from gum olibanum was reported by Chowdary et al 16 With increase in the concentration of gum olibanum in the matrix prepared with combinations of polymers, drug release increased. This observed phenomenon is best explained on the basis of the hydrophilic properties of the polymers.…”
Section: Model Dependent and Independent Analysissupporting
confidence: 82%
See 2 more Smart Citations
“…Ether soluble resin extracted from olibanum exhibited excellent release retarding properties in microentrapment for controlled release due to its hydrophobic water repellant properties. Preliminary studies indicated that the resin has good film forming property when dried from chloroform 7 solution . In the present work the resin extracted from the olibanum was evaluated as coating material in microentrapment.…”
Section: Introductionmentioning
confidence: 99%